Hepatic epithelioid hemangioendothelioma—a single-institution experience with 51 cases - Feng, Lei; Li, Manjie; Huang, Zhuo; Xu, Mingqing (Frontiers in Oncology, 2023)
Objectives: The aim of the present study was to describe the experience at a single institution in the management of hepatic epithelioid hemangioendothelioma (HEHE). Methods: We included 51 patients with histologically confirmed HEHE. We performed Log-rank (Cox-Mantel) survival analyses using Kaplan-Meier methods to test differences in survival between patients in different groups. Univariate Cox regression analyses and multivariate proportional hazards regression model were carried out to identify independent prognostic factors. Results: Different imaging modalities were used to diagnose HEHE with various presentation. Liver resection (LR), liver transplantation (LT), systemic treatment (ST), and surveillance had been used in our study. A significant difference was noted between LR group and surveillance group with respect to mean survival (P=0.006), as was in LR group and ST group (P=0.036) and in surgical approach (LR and LT) and nonsurgical approach (ST and surveillance) (P=0.008). The mean survival between ST group and surveillance group was not significantly different (P=0.851). LR (P=0.010) and surgical approach (P=0.014) were favorable predictors of outcome, while macrovascular invasion (MaVI) (P=0.037), lung metastasis (P=0.040) and surveillance (P=0.033) were poor prognostic factors in univariate analysis. Multivariate analysis showed that LR(P=0.010) and surgical approach (P=0.014) were independently associated with good OS, while surveillance (P=0.033) was independently associated with poor OS. After adjusting for confounding factors, patients in LR group have much better OS than those in surveillance group (P=0.013). However, there was no significant difference in OS between LR group and ST group (P=0.254), as was in ST group and surveillance group (P=0.857). Conclusions: The definitive diagnosis of HEHE was dependent on histopathology, and it was not possible to make a specific diagnosis without biopsy because the radiological findings were similar to those in some hepatic malignancies. ST was not recommended for patients who were not candidates for surgical approaches, and surgical approaches should be warranted regardless of disease stage. The retrospective nature and the small size of the data limited the generalizability of the study, designing a worldwide data base that contains all data about patients with HEHE independent to their therapy was highly recommended.